Use of exochorion characters for the systematics of Hamadryas Hübner and Ectima Doubleday (Nymphalidae: Biblidinae: Ageroniini) - Nieves-Uribe, Sandra; Flores-Gallardo, Adrián; Llorente-Bousquets, Jorge; Luis-Martínez, Armando; Pozo, Carmen (Zootaxa, 2019)
We studied the chorionic morphology of six species of Hamadryas, and together with previous studies, we compared our results with previously published phylogenies for the genus. Samples were obtained from 19 females collected between 2013 and 2017 whose abdomens were sectioned and preserved for later dissection. Eggs were extracted from those dissections and used for the descriptions and illustrations of the chorion. The Hamadryas egg is of the globose type; it is quasi-spheroidal and has multiple polygonal grids with differentiation in specific zones/regions, and knolls with macrocells in their summits that arise in the apical third. These characteristics are very different from those found in the majority of Biblidinae and for those reported in the literature for Batesia and Panacea, which belong to the same subtribe as Hamadryas (Ageroniina, now Ageroniini). Chorionic characters support a previously suggested division of the genus (februa, feronia and laodamia groups) and they agree with the phylogenetic proposal based on morphological characters. Our study expands previous morphological work focused on this genus and compiles all the information available to date about the exochorion of Hamadryas, which now includes data for 10 species and that of Ectima thecla thecla, the putative sister group of Hamadryas.